Studi Analisis Perubahan Debit dan Tekanan Air Pada Pemodelan Pembangkit Listrik Tenaga Mikro Hidro - krishnastana, angga kharisma; Jasa, Lie; Weking, Antonius Ibi (Majalah Ilmiah Teknologi Elektro, 2018)
Micro-Hidro power plant (PLTMH) is one of the alternative sources of power plant that use renewable energy in the form of water. This study analyzes the influence of change in water discharge and the water pressure against the torque, voltage, and the resulting electric current from generator. The result of the analysis on the changes of water discharge as well as changes in water pressure at the angle of the nozzle position 65 0 and variation of nozzle 5 0 ; 65 0 , the highest measurement result obtained on a half-circle vanes. On testing the changes of water discharge or water pressure, output voltage and the output current of the generator which is obtained on the half-circle vanes with the position of the nozzle 65 0 i.e. of 1,994 Volt and 0,332 Ampere on changes of water discharge, as well as 1,326 Volt and 0,265 Ampere on changes of water pressure. Highest torque value is present on the vanes fins with nozzle variation 5 0 ; 65 0 namely 0.0159 Nm on the changes of water discharge and 0.0122 Nm on the changes of water pressure.